The Effect of Strategic Partnerships in Outsourcing Relationships among Large Scale Food Processors in Kenya - Sanita Mulewa, Susan Mary; Mwirigi, Dr. Fred Mugambi; Hood Ahmed, Dr. Anwar (IJRDO - Journal of Business Management, 2017)
The purpose of this study was to establish the effects of strategic partnerships in outsourcing relationships among large sale food processors in Kenya. A quantitative research was adopted using a survey design. The target population was the 181 large scale food processors in Kenya registered under Kenya Association of Manufactures. The large scale food processing firms for each category of the study were selected using stratified random sampling. This study worked with a sample size of 123 large scale food processors representing 68% of the large scale food processing firms in Kenya. The questionnaire was the primary data tool. Through analyzing data, the study found a strong positive correlation between strategic partnerships and outsourcing relationship and ultimately concluded that (r =0.822) whose significant value was 0.000 being less than 0.05.Therefore, it concluded that there is a significant relationship between strategic partnerships and outsourcing relationships.